Nursing Care For Patients with Congestive Heart Failure (Chf) By Giving 45 Head Up Position to Overcome The Problem Of Ineffective Breathing Patterns at RSUD General Ahmad Yani Metro City - Yulistiarini; Sugiarto, Sugiarto; Wardoyo, Eko (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: This study is to determine the nursing care of Congestive Heart Failure (CHF) patients with nursing problems of ineffective breathing patterns with nursing interventions for head up 45o at Jenderal Ahmad Yani Metro Hospital. Method: Data collection using surgical nursing care assessment sheets and oxygen saturation observation sheets. The study used Congestive Heart Failure (CHF) patients. Result: The results of nursing care obtained the results of evaluations that researchers conducted on clients based on the criteria that researchers compiled against 3 diagnoses, the resolved diagnoses were ineffective breathing patterns, decreased cardiac output and activity intolerance. Diagnoses of ineffective breathing patterns experienced an increase in oxygen saturation which was initially 89% after being given a 45o head up position to 99%. Conclusion: Suggestions for patients and families can apply the 45o head up position when experiencing shortness of breath at home and remain compliant with taking medication.